Analisis Faktor Penentu Keberhasilan serta Dampak dari Kelompok Usaha Bersama di Jawa Barat - Priadana, Moh. Sidik; Guntur, Effendi (Jurnal Trikonomika, 2010)
Poverty is a problem that need to be addressed in a multi-sectoral, sustainable and synergistic. Ministry of Social Affairs has introduced a Kelompok Usaha Bersama (KUBE) as one of the institutions to increase household incomes and reducing poverty. Therefore, it is necessary to study what are the factors that the determinant of the success of KUBE. The research should also extent to the success of KUBE impact on increasing household incomes and poverty alleviation, especially in West Java Province. This study aims to obtain empirical evidence of critical success of KUBE and its implications for society and the increase in income poverty reduction in West Java Province. The method used is survey with research hypothesis testing.Measuring perceptions of research variables taken against the perpetrators KUBE. In this measurement, the questionnaire were randomly distributed to 225 respondents. Methods of data analysis used was path analysis to test the research hypothesis. The conclusion of this research are: (i) KUBE critical success factors are: entrepreneurship, institutional quality, capital adequacy, education and training, strategic partnerships, and regulatory and organizational systems, (ii) The six factors are significant determinants of the success of KUBE, either simultaneously or partially, (iii) The success of KUBE has a significant influence on increasing peopleâs income, (iv) The success of KUBE also has a significant influence on poverty alleviation.